The relationship between mathematics attitude and creative thinking among secondary students - Ibrahim, Hasniza; Kamarulzaman, Wirawani; Ismail, Halim; Muhamad Sani, Nur Syaza Afrina (Universiti Sultan Zainal Abidin, Malaysia, 2025)
Background and Purpose: This study aims to examine the levels of mathematics attitudes and creative thinking among Malaysian secondary school students and to explore the relationship between these two factors. The goal is to provide valuable insights and recommendations to enhance the overall quality of mathematics education in Malaysia. Methodology: A quantitative research design was adopted, using a survey as the primary method of data collection. Data were collected from 531 secondary school students in Selangor and Kuala Lumpur through a validated instrument that is Mathematics Attitude and Creative Thinking Scale (MACTS). Descriptive and inferential statistical analyses were conducted using SPSS. Findings: The findings indicate that the overall levels of mathematics attitude (M = 3.26, SD = 0.71) and creative thinking (M = 3.28, SD = 0.69) among Malaysian secondary school students were at a middle high level. Additionally, the study revealed a significant positive correlation (r = 0.70, p < 0.001) between students' attitudes toward mathematics and their creative thinking skills. Contributions: This study provides significant contributions to both theory and practice in mathematics education. Theoretically, it enriches the existing literature by exploring the relationship between mathematics attitudes and creative thinking skills within the Malaysian secondary school context. Practically, it provides valuable information for teachers, curriculum developers, and policymakers